Qur’anic general account on the Arab Jahiliyyah’s socio-economic life - Abdul Ghafar Haji Don (Penerbit Universiti Kebangsaan Malaysia, 1999)
Much has been written concerning the Arab jahiliyyah’s life which lay great emphasis on historical perspective. Ibn Hisham in his al-Sirah al-Nabawiyyah and Ibn Ishaq in Kitab al-Siyar wa al-Maghazi have been regarded as two authentic sources which are discussing the related theme. Besides these two references, there are other books on Sirah which are also highlighting the jahiliyyah life. The prominent of them are Al-Bidayah Wa al-Nihayah by Ibn Kathir, Al-Kamil fi al-Tarikh by Ibn Athir and Al-Mufassol Fi Tarikh al-cArab Qabl al-Islam by Dr Jawad cAli. The principal aim of this article is to explore several aspects of the Arab’s socio-economy life during jahiliyyah’ s (ignorance) period strictly in the light of the Qur’an. As there are many Qur’anic commentaries related to the theme, it is not difficult to comprehend this particular issue